CYRIL AND METHODIUS AS PRECURSORS OF THE ‘RUS’ WORLD’: THE IMAGE OF THE SOLUN BROTHERS AND RUSSIAN IMPERIALISM - Składanowski, Marcin (Forum Teologiczne, 2023)
This article analyses the recent Russian Orthodox discourse on the Solun Brothers. This analysis shows, on the one hand, that the politicised interpretation of the mission of Cyril and Methodius is not a recent ideological innovation, but appeals to the same motives that made their cult popular in 19th-century Russian Orthodoxy. On the other hand, the reinterpretation of the meaning of their mission that is currently taking place is acquiring additional political objectives harmonised with those of Russian state ideology, as well as cultural and foreign policy, especially in relation to the post-Soviet area. At the same time, however, the religious significance of Cyril and Methodius is almost disappearing from church discourse and theological reflection. A common element of Russian discourse on the Solun Brothers, in both the 19th and 21st centuries, is ahistoricity, understood as a complete disconnection from the actual historical context in which Cyril and Methodius lived and worked .